Vibrational study on Zn(Pyrimidine)(2)Cl-2, Pyrimidine-Al(OH)(3) and Pyrimidine-(Al(OH)(3))(2) complexes - Akalın, Elif; AKYÜZ, SEVİM (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2008)
A molecular modeling analysis was performed via density functional theory (DFT), using B3LYP/6-31++G(d,p) basis set on Zn(PM)(2)Cl-2, PMAI(OH)(3) and PM-(AI(OH)(3))(2) complexes (PM: Pyrimidine) in order to investigate monodentate and bidentate coordination effects on pyrimidine vibrational wavenumbers. The Zn(PM)(2)Cl-2. Complex was synthesized and the FT-IR and FT-Ra spectra were recorded which, when compared to the calculated wavenumbcrs of the model mono- and bidentate Al(OH)(3) Complexes, showed that pyrimidine behaved as a rnonodentate ligand. Anharmonic corrections to the calculated wavenumbers of the Zn(PM)(2)Cl-2 complex were done and the results led to a good overall agreement with the observed wavenurnbers. A complete assignment of the fundamentals was proposed based on the internal mode analysis done by Gaussian03 programme. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Pyrimidine complexes; Density functional theory; DFT; Anharmonic wavenumbers; Infrared and Raman spectra; crystal; thermochemistry; zinc(II); pirimidin kompleksleri; Yoğunluk fonksiyonel teorisi; harmonik olmayan dalgasayıları; Infrared ve Raman spektrumları; kristal; termokimya; çinko (II)